Role of Probiotics in Patients with Allergic Rhinitis: A Systematic Review of Systematic Reviews - Iftikhar, Haissan; Awan, Muhammad Ozair; Awan, Muhammad Sohail; Mustafa, Khawaja; Das, Jai K.; Ahmed, Shahzada Khuram (International Archives of Otorhinolaryngology, 2022)
Introduction Allergic rhinitis (AR) is estimated to affect up to 30% of the world population. With the rise in cases, newer treatment modalities have been explored. Probiotics have shown to reduce symptoms of AR and improve quality of life. A few systematic reviews have been published aiming to assess the role of probiotics in AR.Objectives To consolidate the recent evidence with an overview of systematic reviews by extracting data regarding subjective outcomes (from quality of life questionnaires, the Total Nasal Symptom Score, the Total Ocular Symptom Score, the Daily Total Symptom Score, the incidence of AR, and the Rhinitis Total Symptom Score) and objective outcomes (levels of antigen-specific immunoglobulin E [IgE], total IgE, interleukin 10 [IL-10], interferon gamma [IFNG], eosinophil, and the T helper 1/T helper 2 [Th1/Th2] ratio).Data Synthesis We conducted a literature search on the PubMed, EBSCO CINAHL, EBSCO Dentistry & Oral Sciences Source, and Cochrane Library up to April 14, 2020. The qualitative assessment was performed using the Assessing the Methodological Quality of Systematic Reviews (AMSTAR-2) tool. A total of 419 titles were screened, and 3 systematic reviews met our eligibility criteria. Probiotics in the treatment of AR have been shown to improve quality of life, the total nasal and ocular symptom scores, the daily total symptom scores and Th1/Th2 ratio. No difference was ascertained for rhinitis total symptom score, and the rates of antigen-specific IgE, total IgE, IL-10, INFG and eosinophil.Conclusion The present review showed that there is considerable evidence that probiotics are useful in the treatment of AR. Further randomized trials targeting the limitations of the currently-available evidence can help ascertain the usefulness of probiotics in cases of AR.
Keywords: allergic rhinitis; probiotics; nasal symptom score; quality of life; rhinosinusitis